2015
DOI: 10.1017/s1352465815000351
|View full text |Cite
|
Sign up to set email alerts
|

An experimental Investigation of the Impact of Personality Disorder Diagnosis on Clinicians: Can We See Past the Borderline?

Abstract: Diagnostic labels may negatively impact on clinicians' judgments and perceptions of individuals and therefore clinicians should think carefully about whether, and how, they use diagnoses and efforts should be made to destigmatize diagnostic terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
1
25
1
Order By: Relevance
“… 10 11 Further, diagnostic labels allow clinicians to assume homogeneity among members of patient groups, in addition to providing an efficient method for health professionals to communicate. 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 11 Further, diagnostic labels allow clinicians to assume homogeneity among members of patient groups, in addition to providing an efficient method for health professionals to communicate. 12 …”
Section: Introductionmentioning
confidence: 99%
“… 3 A study investigating the impact of labelling borderline personality disorder on clinician interpretation of patient symptoms found clinicians’ prior awareness of a diagnosis of borderline personality disorder, compared to no awareness, resulted in a tendency to frame observations of the individual in terms of the label, and a failure to observe positive behaviours. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The label of personality disorder is a controversial one. It can be stigmatising, can mask the problems it is supposed to help address, and can add to the problems that people with the label experience (Bodner et al, 2015;Lam et al, 2016). Nevertheless, where access to mental health services is contingent on a psychiatric diagnosis, a label of personality disorder can be the only way that some people can access help.…”
Section: Introductionmentioning
confidence: 99%
“…National guidelines in the UK state that professionals working with people with a personality disorder diagnosis should function in an "engaging, open and non-judgemental manner" and foster "an atmosphere of hope and optimism" (National Institute for Health and Care Excellence, 2009, p. 6), however, there is abundant evidence that health care professionals often hold negative attitudes (Chartonas, Kyratsous, Dracass, Lee, & Bhui, 2017;Sansone & Sansone, 2013;Westwood & Baker, 2010). For example, several studies have found that people with a diagnosis of personality disorder are often seen by professionals as more difficult (James & Cowman, 2007;Lewis & Appleby, 1988;McGrath & Dowling, 2012) and less likely to engage in treatment (Lam, Poplavskaya, Salkovskis, Hogg, & Panting, 2016). Studies have also found that negative attitudes can lead to poorer care including less empathic responses (K. Fraser & Gallop, 1993;McGrath & Dowling, 2012) and inadequate service provision (James & Cowman, 2007;Lam et al, 2016).…”
mentioning
confidence: 99%
“…For example, several studies have found that people with a diagnosis of personality disorder are often seen by professionals as more difficult (James & Cowman, 2007;Lewis & Appleby, 1988;McGrath & Dowling, 2012) and less likely to engage in treatment (Lam, Poplavskaya, Salkovskis, Hogg, & Panting, 2016). Studies have also found that negative attitudes can lead to poorer care including less empathic responses (K. Fraser & Gallop, 1993;McGrath & Dowling, 2012) and inadequate service provision (James & Cowman, 2007;Lam et al, 2016). Negative attitudes have also been found to be associated with reduced staff well-being (Taylor, 2011).…”
mentioning
confidence: 99%